A combination of recombinase polymerase amplification with CRISPR technology rapidly detects goose parvovirus with high accuracy and sensitivity - Xiuqin Chen; Shizhong Zhang; Su Lin; Shao Wang; Meiqing Huang; Shaoying Chen; Shilong Chen (Frontiers in Cellular and Infection Microbiology)
BackgroundGoose parvovirus (GPV) poses a significant threat to the waterfowl industry, necessitating reliable detection methods. However, conventional techniques are often time-consuming, equipment-dependent, or lack sufficient sensitivity for detecting early-stage infection. In contrast, emerging CRISPR/Cas12a-based systems offer a promising alternative for rapid, sensitive, and on-site diagnostics.MethodsWe developed and optimized a recombinase polymerase amplification (RPA)-CRISPR/Cas12a assay targeting the conserved VP3 gene of GPV. The analytical and diagnostic performance of this assay was rigorously validated using plasmid standards and clinical specimens from both experimentally infected and field-collected ducklings.ResultsOur developed assay combines RPA with CRISPR/Cas12a technology for rapid GPV nucleic acids detection. This method achieves a detection limit of 10 copies/μL of the VP3 gene within one hour, demonstrating high sensitivity and rapid turnaround. The assay exhibited exceptional specificity, with no cross-reactivity against other waterfowl viruses, and showed robust reproducibility, with intra- and inter-assay coefficients of variation consistently below 5.0%. Clinical validation using 42 field samples confirmed a diagnostic sensitivity of 100% and 95.5% specificity, showing superior performance to real-time quantitative PCR (qPCR) in both metrics. Furthermore, the assay supports flexible visual readouts using portable blue light transilluminators, facilitating on-site interpretation.ConclusionsThis study established a highly field-deployable RPA-CRISPR/Cas12a assay for rapid, visual detection of GPV with outstanding sensitivity and specificity. Its capability for instrument-free on-site diagnosis via blue light transillumination makes this approach particularly promising for resource-limited settings.